Photography and death : framing death throughout history - Harris, Racheal (Emerald Publishing Limited, 2020)
Examining a spectrum of post-mortem images, this volume considers what death photography communicates about attitudes related to dying, mourning and the afterlife. Focusing on American examples, topics are discussed alongside contemporary representations of death, as seen in celebrity death images and forensic photography.
Includes index.
Keywords: Postmortem photography -- Psychological aspects.; Death -- Psychological aspects.; Photography, Subjects & Themes -- General.; Special kinds of photography.; elektronické knihy; electronic books